Legal Certainty And Integrity Of Bank Asset Quality Assessment: A Critical Review Of Collateral Appraiser Independence - Fauzan Ananda; Wahyu Mahendra (Faculty of Law, University of Mataram, 2026)
This study aims to examine the implementation of collateral appraiser independence and the integrity of bank asset quality assessment as regulated under POJK No. 40/POJK.03/2019, as well as to analyze its consistency with the principles of equality, proportionality, legal certainty, non-discrimination, and professional protection. In addition, this study examines potential legal uncertainty and practical implications arising from differences in the regulation of internal bank appraisers and independent appraisers, particularly in collateral valuation below and above the threshold of Rp10 billion. This research employs a normative legal research method (doctrinal legal research) by focusing on the analysis of legislation and legal doctrines related to collateral valuation and the integrity of bank asset quality assessment. The findings show that POJK No. 40/POJK.03/2019 provides a legal framework that emphasizes the importance of independent valuation for high-value collateral exceeding Rp10 billion. However, the difference in authority between internal bank appraisers and independent appraisers still creates legal uncertainty, particularly regarding the application of valuation standards, verification procedures, and the determination of collateral value thresholds. This condition may lead to valuation bias, inconsistency in asset quality, and challenges in complying with professional appraisal standards. Therefore, regulatory harmonization is needed through more detailed guidelines concerning the authority, responsibilities, independence requirements, verification mechanisms, and periodic evaluation of the collateral value threshold.